This should really be a straightforward calculation, but somehow, I keep confusing myself and failing over and over again. I did the calculation so many times that I don't even know what I'm looking at anymore. Some help would be greatly appreciated.

Let me show you what I tried to do, so you can check my understanding (or lack thereof).

(1 + 2 $\rightarrow$ 1' + 2') elastic scattering in the LAB frame
This means: $$ m_1 = m_1'$$ $$m_2 = m_2'$$ $$\mathbf{p_2} = \mathbf{ 0}$$ As you can see, we choose to work in the rest frame of particle 2 before the scattering.

I managed to calculate the differential cross section in the CM (center of mass) frame, which is (in natural units): $$\left( \frac{d\sigma}{d \Omega }\right)_{CM} = \frac{|\mathcal{M}|^2}{(8 \pi)^2 E_{CM}^2}$$ Here, $\mathcal{M}$ is the invariant amplitude and $E_{CM}=E_1 + E_2 = E_1' + E_2'$.

Following the technique used in the CM frame, I use these known relations: $$ d\sigma = \frac{V}{T} \frac{dP}{|\mathbf{v_1} - \mathbf{v_2}|}$$ $$dP = \frac{|\left< f | S|i\right>|^2}{\left< f | f\right> \left<i | i\right>} d\Pi$$ $$\implies d\sigma = \frac{|\mathcal{M}|^2}{(2E_1)(2E_2)|\mathbf{v_1} - \mathbf{v_2}|}d\Pi_{LIPS}$$ This leads me to $$d\sigma = \frac{|\mathcal{M}|^2}{4 E_1 E_2|\mathbf{v_1} - \mathbf{v_2}|} (2\pi)^4 \delta^4(p_1' + p_2' - p_1 - p_2) \frac{d^3 \mathbf{p}_1'}{(2\pi)^3 2 E_1'} \frac{d^3 \mathbf{p}_2'}{(2\pi)^3 2 E_2'} $$ Using $p_2 = m_2$ and integrating over the momenta for particle 2, $$d\sigma = \frac{|\mathcal{M}|^2}{(8 \pi)^2 E_1 m_2|\mathbf{v_1} - \mathbf{v_2}|} \delta(E_1' + E_2' - E_1 - m_2) \frac{d^3 \mathbf{p}_1'}{E_1' E_2'} $$ Next, I switch to spherical coordinates, $d^3 \mathbf{p}_1' = d\Omega \, p^2 dp$ and I factor out the solid angle differential. Finally, I plug in the integral for the remaining degree of freedom $(p)$, to get this: $$\left( \frac{d\sigma}{d \Omega }\right)_{CM} = \frac{1}{(8 \pi)^2 E_1 m_2|\mathbf{v_1} - \mathbf{v_2}|} \int_0^\infty \frac{dp \, p^2 }{E_1' E_2'} |\mathcal{M}|^2 \delta(E_1' + E_2' - E_1 - m_2) $$ This is where I get confused... I tried defining a new variable $x=E_1' + E_2' - E_1 - m_2$ and substituting it in the integral, but everything always gets messy because both $E_1'$ and $E_2'$ depend on $p=|\mathbf{p}_1'|$: $$E_1' = \sqrt{m_1^2 + p^2}$$ $$E_2' = \sqrt{m_2^2 + (\mathbf{p}_1 - \mathbf{p}_1')^2}$$

Messy, messy, messy... so I tried to do it another way:

I recast the CM formula in a Lorentz-covariant form (for known $\mathbf{p}_1$) using Mandelstam variables, i.e. $$ s = (p_1 + p_2)^2 = (p_1' + p_2')^2$$ $$ t = (p_1 - p_1')^2 = (p_2 - p_2')^2$$ $$ dt = 2 | \mathbf{p}_1| \, |\mathbf{p}_1'| \frac{d \Omega_{CM}}{2 \pi}$$ $$\implies \frac{d \sigma}{dt} = \frac{|\mathcal{M}|^2}{64 \pi s |\mathbf{p_1}|^2}$$

Next, I write $s$ and $t$ in the LAB frame in hopes of getting the correct formula, but to no avail... I get something extremely complicated or something simply wrong...

THIS is what I should get at the end, but I can't seem to get it: $$\left( \frac{d\sigma}{d \Omega }\right)_{LAB} = \frac{|\mathcal{M}|^2}{(8 \pi)^2} \frac{|\mathbf{p}_1'|^2}{|\mathbf{p}_1|} \frac{1}{m_2 (E_1 + m_2) \big| |\mathbf{p}_1'| - |\mathbf{p}_1| E_1' \cos{\theta} \big|}$$

So, what do you think?


I consider the scattering process $A+B \to 1 + 2$. The differential cross-section is always given by \begin{equation} \begin{split}\label{eq1} d\sigma &= \frac{1}{(2E_A)(2E_B)|v_A - v_B|} \frac{d^3p_1}{(2\pi)^3} \frac{1}{2E_1} \frac{d^3p_2}{(2\pi)^3} \frac{1}{2E_2} \left| {\cal M} \right|^2(2\pi)^4 \delta^4( p_A + p_B - p_1 - p_2) \end{split} \end{equation}

The take $B$ to be at rest. Thus $p_B^\mu = (m_B,0,0,0)$ and $p_A^\mu = (E_A, \vec{p}_A)$. Plugging this into the equation above, we get \begin{equation} \begin{split} d\sigma &= \frac{1}{(2p_A)(2m_B)} \frac{d^3p_1}{(2\pi)^3} \frac{1}{2E_1} \frac{d^3p_2}{(2\pi)^3} \frac{1}{2E_2} \left| {\cal M} \right|^2(2\pi)^4 \delta^4( p_A + p_B - p_1 - p_2) \end{split} \end{equation} where we have used $|\vec{v}_A| = \frac{p_A}{E_A}$. We can integrate over $\vec{p}_2$ to get \begin{equation} \begin{split} d\sigma &= \frac{1}{(2p_A)(2m_B)} \frac{d^3p_1}{(2\pi)^2} \frac{1}{2E_1} \left| {\cal M} \right|^2 \frac{1}{2E_2} \delta(E_A + m_B - E_1 - E_2) \\ \frac{d\sigma}{d\Omega} &= \frac{1}{(2\pi)^2(2p_A)(2m_B)} dp_1 p_1^2 \frac{1}{2E_1} \left| {\cal M} \right|^2 \frac{1}{2E_2} \delta(E_A + m_B - E_1 - E_2) \end{split} \end{equation} where $E_2^2 = (\vec{p}_1 - \vec{p}_A)^2 + m_2^2 = p_1^2 + p_A^2 - 2 p_1 p_A \cos\theta + m_2^2 $ and $E_1^2 = p_1^2 + m_1^2$. To integrate over $p_1$, we see that the $\delta$-function becomes \begin{equation} \begin{split} \delta & \left(E_A + m_B - \sqrt{p_1^2 + m_1^2} - \sqrt{p_1^2 - 2 p_1 p_A \cos\theta + p_A^2 + m_2^2 }\right) \\ &= \delta (p_1 - p_f) \left(\frac{p_f}{E_1} + \frac{p_f - p_A\cos\theta}{E_2} \right)^{-1} \end{split} \end{equation} where $p_1 = p_f$ is the solution to the argument in the delta function. Integrating over $p_1$, we get \begin{equation} \begin{split} \boxed { \frac{d\sigma}{d\Omega} = \frac{1 }{64\pi^2m_B} \left[ E_2 + E_1\left(1 - \frac{p_i}{p_f} \cos\theta\right)\right]^{-1} \frac{p_f}{p_i}\left| {\cal M} \right|^2 } \end{split} \end{equation} where $E_1 = \sqrt{p_f^2 + m_1^2}$, $E_2 = \sqrt{(\vec{p}_f - \vec{p}_i)^2 + m_2^2}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.